The System of Quality Control of Education in Domestic Schools - Gavkhar Umarovna Radjabova; Ramzxon Rashidovich Jalilov (Peerian Journals Publishing, 2022)
The article substantiates in detail the relevance of the problem of control and management of the quality of education. Control and monitoring of the quality of education make it possible to modernize the system of the Uzbek educational process in a timely manner. This is laying the foundation at the stage of building the building of an economically and politically effective legal state. It is not so much about monitoring the knowledge, skills and abilities of students, but about the quality of the system itself and teaching methods.
Keywords: Monitoring; control; quality of education; current control